2006
DOI: 10.1038/sj.jidsymp.5650011
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Role for Calreticulin in the Enhancement of Wound Healing through Multiple Biological Effects

Abstract: Calreticulin (CRT), an intracellular chaperone protein crucial for the proper folding and transport of proteins through the endoplasmic reticulum, has more recent acclaim as a critical regulator of extracellular functions, particularly in mediating cellular migration and as a requirement for phagocytosis of apoptotic cells. Consistent with these functions, we show that the topical application of CRT has profound effects on the process of wound healing by causing a dose-dependent increase in epithelial migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 60 publications
3
42
0
1
Order By: Relevance
“…Overexpression of CRT-enhanced wound closure by stimulating cell migration in human keratinocytes and fibroblasts (Gold et al, 2006). In both murine-and porcineimpaired animal models of skin injury, CRT increased epithelial migration and granulation tissue formation (Gold et al, 2006;Hayashida et al, 2006). In this study, we showed that CRT knockdown decreased the migration and invasion capacity of ESCC cells with accompanying repression of CTTN protein levels.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Overexpression of CRT-enhanced wound closure by stimulating cell migration in human keratinocytes and fibroblasts (Gold et al, 2006). In both murine-and porcineimpaired animal models of skin injury, CRT increased epithelial migration and granulation tissue formation (Gold et al, 2006;Hayashida et al, 2006). In this study, we showed that CRT knockdown decreased the migration and invasion capacity of ESCC cells with accompanying repression of CTTN protein levels.…”
Section: Discussionmentioning
confidence: 55%
“…CRT is known to bind to the C-terminal cytoplasmic tail KXGFFKR sequence motif of a 2 -integrin. Overexpression of CRT-enhanced wound closure by stimulating cell migration in human keratinocytes and fibroblasts (Gold et al, 2006). In both murine-and porcineimpaired animal models of skin injury, CRT increased epithelial migration and granulation tissue formation (Gold et al, 2006;Hayashida et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complementary in vitro experiments showing the effect of CRT on cellular migration and proliferation, two key processes that enable wound repair, provide a mechanistic explanation for the accelerated and enhanced effect observed of CRT on porcine wound repair. In companion studies, in which we used a diabetic murine model of excisional cutaneous repair, 4,84 we obtained the same biological effects with the identical pharmacological dose (5.0 mg/ml) of CRT on parameters of wound repair as shown herein in the porcine model. Further understanding the mechanisms of action of CRT (eg, receptors, signaling pathways, domain structure/ function) on keratinocytes, fibroblasts, endothelial cells, and monocytes/macrophages from both intracellular and extracellular perspectives is important for a better understanding of the in-depth role of CRT as a stress/injuryinduced protein with significant impact on a diverse range of reparative responses.…”
Section: Discussionmentioning
confidence: 83%
“…CRT resides mainly in the ER and is a Ca 2Ï© -binding protein that function as a Ca 2Ï© buffer and molecular chaperone, although it has also been linked to a number of processes occurring outside the ER lumen (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which implies other subcellular localizations for CRT other than the ER. However, the subcellular origin, biochemical features, and the precise molecular mechanism responsible for targeting CRT to the plasma membrane is not fully understood.…”
mentioning
confidence: 99%